2017
DOI: 10.1186/s12959-016-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variation rs6903956 in the novel androgen-dependent tissue factor pathway inhibitor regulating protein (ADTRP) gene is not associated with levels of plasma coagulation factors in the Singaporean Chinese

Abstract: BackgroundGenome-wide association study (GWAS) has reported that rs6903956 within the first intron of androgen-dependent tissue factor pathway inhibitor (TFPI) regulating protein (ADTRP) gene is associated with coronary artery disease (CAD) risk in the Chinese population. Although ADTRP is believed to be involved in the upregulation of TFPI, the underlying mechanism involved is largely unknown. This study investigated the association of rs6903956 with plasma Factor VII coagulant activity (FVIIc) and fibrinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Our findings are in line with previously reported improved ACVD clinical parameters such as systolic blood pressure and triglycerides. 12 , 13 This suggests that non-surgical periodontal treatment synergistically affects ACVD profiles, periodontal inflammatory parameters and NET degradation. Unraveling NET formation and degradation mechanisms in periodontitis patients may improve the understanding of the pathophysiology of periodontitis and the aetiopathogenetic links between periodontitis and its systemic co-morbidities such as ACVD, while also enabling the development of new therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with previously reported improved ACVD clinical parameters such as systolic blood pressure and triglycerides. 12 , 13 This suggests that non-surgical periodontal treatment synergistically affects ACVD profiles, periodontal inflammatory parameters and NET degradation. Unraveling NET formation and degradation mechanisms in periodontitis patients may improve the understanding of the pathophysiology of periodontitis and the aetiopathogenetic links between periodontitis and its systemic co-morbidities such as ACVD, while also enabling the development of new therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Nevertheless, previous research has shown beneficial effects of non-surgical periodontal therapy on several clinical and biochemical parameters of ACVD, including flow-mediated dilatation, intima media thickness, systolic blood pressure, and a decrease in activated platelets. 8 14 Altogether, this may reduce the risk factors of an ACVD profile of periodontitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Available perioperative data are principally generated from RCT substudies and considering the DOAC pharmacokinetics parameters (short time to peak effect and short half-life), periprocedural bridging is usually not required ( Dubois et al, 2017 ). However, decisions in elective situations about stopping DOACs perioperatively should be based on the thromboembolic risk of the patient as well as general characteristics, the bleeding risk of the invasive procedures, and the DOAC pharmacokinetics profile.…”
Section: Bridging In Procedural Management and Reversal Agentsmentioning
confidence: 99%